2024
DOI: 10.1039/d3tb02714g
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared light-actuated on-demand botanicals release and hyperthermia by an antibiotic-free polysaccharide-based hydrogel dressing for the synergistic treatment of wound infections

Shuwen Sun,
Wenbo Lin,
Lu Yang
et al.

Abstract: Bacterial infection is a key factor for affecting wound healing. Conventional treatments might lead to the widespread emergence of drug-resistant bacteria due to the long-term and excessive use of antibiotics....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Among them, the cytotoxicity of cells remained relatively low when exposed to low doses of nanocomposites under pH 7.4 and NIR-free irradiation. The hemolysis rates based on the nanomaterials were all below 5%, which strongly confirmed that the prepared nanocomposites have excellent biocompatibility. These results were similar to the above results of bacterial activity measured at pH 7.4 without NIR, signifying the excellent biocompatibility and biosafety of MXene/ZIF-90@ICG, and can be further used for in vivo relevant antimicrobial studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the cytotoxicity of cells remained relatively low when exposed to low doses of nanocomposites under pH 7.4 and NIR-free irradiation. The hemolysis rates based on the nanomaterials were all below 5%, which strongly confirmed that the prepared nanocomposites have excellent biocompatibility. These results were similar to the above results of bacterial activity measured at pH 7.4 without NIR, signifying the excellent biocompatibility and biosafety of MXene/ZIF-90@ICG, and can be further used for in vivo relevant antimicrobial studies.…”
Section: Resultsmentioning
confidence: 99%
“…The development of computed tomography, ultrasound imaging and magnetic resonance imaging as the most prevalent non-invasive imaging techniques has promoted the early diagnosis and monitoring of diseases. 1–4 However, on account of poor specificity, low spatiotemporal resolution, low signal-to-noise ratio, high cost and high risk of ionic radiation, many applications are limited. In contrast, fluorescence optical imaging is a method that combines optical detection with optical probes to image cells or tissues to obtain biological information, with low cost, high sensitivity, high resolution, simple operation and real-time detection, which has broad prospects in basic research and clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, fluorescence optical imaging is a method that combines optical detection with optical probes to image cells or tissues to obtain biological information, with low cost, high sensitivity, high resolution, simple operation and real-time detection, which has broad prospects in basic research and clinical applications. 4–8…”
Section: Introductionmentioning
confidence: 99%